Pengaruh Penggunaan Media Pembelajaran Lettrum Box Untuk Meningkatkan Kemampuan Numerasi Anak Usia Dini - Tita, Tita Bonita Irianfi; Intan Prastihastari Wijaya; Dwiyanti, Linda (Universitas Muhammadiyah Metro, 2025)
This research is motivated by findings at the Mojoroto State Kindergarten, where the basic numeracy skills of early childhood children are still low. Many children are unable to distinguish numbers and count correctly, and there is a lack of use of educational learning media. To address this issue, the researcher created a learning media called